The Liberal Arts Paradox in Higher Education : Negotiating Inclusion and Prestige - Telling, Kathryn (Book collections on Project MUSE., 2023)
By examining the emergence and growth of liberal arts degrees in English higher education, this book tackles one of the key issues in the critical sociology of higher education: the relationship between selective education and elitism.